Polyphenol-Containing Feed Additive Polygain™ Reduces Methane Production and Intensity from Grazing Dairy Cows Measured Using an Inverse-Dispersion Technique - Mei Bai; Pragna Prathap; Muhammed Elayadeth-Meethal; Matthew Flavel; Richard Eckard; Frank R. Dunshea; Richard Osei-Amponsah; Mohammad Javed Ashar; Deli Chen; Surinder Chauhan (Animals)
This study, conducted on a commercial dairy farm using a robotic milking system in Victoria, Australia, examined the effects of Polygain™ (The Product Makers Australia), a polyphenol-rich sugarcane feed material (PRSFM), on CH4 emissions in grazing dairy cattle using an inverse-dispersion model (IDM) combined with open-path laser techniques. Thirty lactating Holstein Friesian cows (aged 2–5 years with an average body weight of 663 kg and average daily milk production of 28.9 kg) were divided into two dietary treatment groups of fifteen cows each. Before the measurement, the PRSFM (0.25%) was supplemented for 3 weeks as an adaptation period and mixed with pellet feed for the treatment group. Over the 2-week measurement period, CH4 production (MP) was 495 ± 12 and 377 ± 12 (mean ± standard error) g CH4/animal/day for the control and treatment groups, respectively. Methane intensity (MI) was 17.04 and 13.01 g CH4/animal/kg milk/day in the control and treatment groups, respectively. On average, Polygain supplementation reduced MP and MI by 24%. This potential CH4 reduction extrapolated across Australia contributes to a 2.63% reduction in national agricultural emissions. This study underscores the potential of Polygain for CH4 mitigation in dairy cattle.